Structure of direct and indirect umbilical hernia and the implication on surgical repair in children - Mohamed Saber Mostafa; Mohamed AbdElrahman; Mohammed Elsherbeny; Hesham El-Safoury (SpringerOpen, 2020)
Abstract Background Umbilical hernia (UH) is one of the most common problems seen by paediatric surgeons. The recurrence rate after surgical repair is 1-2%. In this study, we examined the ring of umbilical hernia histologically to detect differences between the two types of umbilical hernia and the relation between this histologic difference and the technique of surgical repair. Results Fifty paediatric patients of both sexes with clinically diagnosed direct and indirect (oblique) umbilical hernia were collected from the paediatric surgery department in the period between March 2016 and February 2018. Age ranged between 2 and 5 years. Biopsies (5 mm) were taken from the upper, lower, right and left borders of the ring in both types and processed for histological examination. Classification of umbilical hernia was based on Chang-Seok et al.'s classification, which classified the umbilical hernia into three types (direct, oblique and hernia into umbilical cord) which depend on the presence of a hole in the ring and whether the ring is covered by ligamentum teres or not. Histological sections were examined by light microscopy, and data was analysed using chi-square test to detect predominance of one type of collagen fibre over the other in each sample. Transverse collagen fibres were predominant in the upper border of the ring in 15 patients (75%) and the lower border in 14 patients (70%) of direct umbilical hernia. Transverse collagen fibres were also predominant in the right border of the ring in 21 patients (70%) and the left border in 21 patients (70%) of indirect umbilical hernia. This predominance in both cases was found to be statistically significant. Conclusions Predominance of transverse collagen fibres in the upper and lower borders of the ring in direct umbilical hernia and predominance in the right and left borders of the ring in oblique umbilical hernia encouraged us to suggest that wound will be more stable if closed in a transverse manner in direct umbilical hernia and a longitudinal manner in oblique umbilical hernia especially in recurrent cases.